D4N2024 Presentation Showcase – THEMATIC SESSION 4a: Making social protection nutrition-sensitive - Neupane, Sumanta; Hazarika, Bhabesh; Chakrabarti, Suman; Kishore, Avinash; Basar, Sk Md Abul; Safdar, Nilofer F.; Prasada, DVP; Gogoi, Pallabi; Singh, Garima; Puri, Raghav; Pingali, Prabhu; Lamisha, Mahjabin Rashid (International Food Policy Research Institute, 2024)
D4N2024 Presentation Showcase – THEMATIC SESSION 4a: Making social protection nutrition-sensitive